2022
DOI: 10.1021/acssuschemeng.1c06335
|View full text |Cite
|
Sign up to set email alerts
|

Promoted Production of Phenolic Monomers from Lignin-First Depolymerization of Lignocellulose over Ru Supported on Biochar by N,P-co-Doping

Abstract: Co-doping of heteroatoms into the support of metal-supported catalysts is a prevalent method to improve the catalytic performance by adjusting metal–support interactions. This paper investigated the catalytic performances of Ru supported on biomass-derived char (Ru@Char), N-doped char (Ru@N-Char), and N,P-co-doped char (Ru@NP-Char) in the emerging lignin-first depolymerization for both poplar (hardwood) and pine (softwood) samples, with an emphasis on the production of phenolic monomers. Various characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…A summary of the literature on the RCF of biomass, including the biomass source, catalysts, operating conditions, degree of delignification, selectivity to lignin monomers and carbohydrates retention is provided in Table 4. 4,15–17,29,54,55,57,58 The degree of delignification and carbohydrate retention are observed to be in the range of 70–95% and 85–95%, respectively. Recently, Liu et al 17 reported 95% delignification and ∼87% retention of the carbohydrate of the birch wood biomass using the N-doped Ru/ZnO/C catalyst at 240 °C and 30 bar initial H 2 partial pressure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A summary of the literature on the RCF of biomass, including the biomass source, catalysts, operating conditions, degree of delignification, selectivity to lignin monomers and carbohydrates retention is provided in Table 4. 4,15–17,29,54,55,57,58 The degree of delignification and carbohydrate retention are observed to be in the range of 70–95% and 85–95%, respectively. Recently, Liu et al 17 reported 95% delignification and ∼87% retention of the carbohydrate of the birch wood biomass using the N-doped Ru/ZnO/C catalyst at 240 °C and 30 bar initial H 2 partial pressure.…”
Section: Resultsmentioning
confidence: 99%
“…52 Therefore, carbon-based catalysts are widely used for RCF of different lignocellulosic biomasses owing to their neutral character. Typically, carbon-supported monometallic Pt, 53 Pd, 16,54 Ru 4,29 and Ni, 55 and bimetallic NiFe 56 catalysts have been evaluated. Zhai et al 56 studied the RCF of birch sawdust using a NiFe bimetallic catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical states of Ru, C, N, and S elements in the three catalysts were studied by XPS measurements. The XPS spectra of Ru 3p 3/2 can be deconvoluted into Ru 0 and Ru n+ species, in which the Ru 0 species had been recognized as the active sites for hydrogenolysis of lignin ( Wu et al, 2021 ; Ding et al, 2022 ). As shown in Figure 4A , the content of Ru 0 species slightly increased from 75.45% (Ru@C) to 78.14% (Ru@CNS-N 2 ), suggesting that the co-doping of nitrogen and sulfur could facilitate the formation of Ru 0 species.…”
Section: Resultsmentioning
confidence: 99%